Errors by paediatric residents in calculating drug doses. Issue 1 (1st July 1998) - Rowe, C; Koren, T; Koren, G
Abstract : BACKGROUND: Errors in calculating drug doses in infants and small children can cause morbidity and mortality, especially with agents exhibiting a narrow therapeutic window. A previous study from this institution has detected potential life threatening errors in calculations performed by trainees while writing prescriptions. OBJECTIVES: To verify whether the true incidence of trainees' errors in prescribing can be explained by impaired calculation skills in written tests. SETTING: A tertiary paediatric hospital; educational rounds for core paediatric residents. METHODS: Two anonymous written tests, which included calculations of doses similar to those performed at the paediatric bedside; one was conducted in 1993 and one in 1995. RESULTS: Thirty four paediatric residents participated in 1993 and 30 in 1995. A substantial number of trainees in both years committed at least one error. In general, there was no correlation between the length of training (0 to 4 years) and likelihood of making a mistake. Three trainees in 1993 and four in 1995 committed 10-fold errors. These seven residents committed significantly more errors than the rest of the group in each of the tests separately. All seven were in their first two years of training, and six were in their first year of residency. CONCLUSIONS: A substantial proportion of paediatric trainees make mistakes while calculating drug doses under optimal test conditions. Some trainees commit 10-fold errors, which may be life threatening. The results of these anonymous tests suggest that testing of calculation skills should be mandatory, and appropriate remedial steps should follow to prevent paediatric patients receiving wrong drug dosages.